Postgraduate training in psychotherapy in Sri Lanka: the need for a systematic approach - Hanwella, Raveen (Sri Lanka Journal of Psychiatry, 2011)
The increase in the availability of biological therapies has led to a decline in the use of psychotherapy in treating psychiatric illnesses. As a result, opportunities for training in psychotherapy have declined. Yet, psychotherapy remains an important, and for some patients, the only therapy. This paper discusses a systematic approach to psychotherapy training for postgraduate trainees in Psychiatry in Sri Lanka.
Keywords: Postgraduate training; systematic approach; Sri Lanka; psychotherapy